1999
DOI: 10.1046/j.1365-2559.1999.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological analysis of 501 non-Hodgkin's lymphomas in Korea according to the Revised European–American Classification of Lymphoid Neoplasms

et al.

Abstract: We conclude that lineage assignment (T vs. B) in the REAL classification is a clinically important distinction, but that it is necessary to subdivide the broad category of DLBCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
40
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 0 publications
12
40
3
Order By: Relevance
“…Our findings are in agreement with previous results, showing the relatively higher proportions of patients with overall NHL and T/NK-cell neoplasms, and the relatively lower proportions of patients with FL, CLL/SLL, and HL among Korean individuals compared with those of Western populations (Supplementary Table III) [4][5][6][7][8][9][10][11][12][13][14][15][16][17]19,21,23,37].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our findings are in agreement with previous results, showing the relatively higher proportions of patients with overall NHL and T/NK-cell neoplasms, and the relatively lower proportions of patients with FL, CLL/SLL, and HL among Korean individuals compared with those of Western populations (Supplementary Table III) [4][5][6][7][8][9][10][11][12][13][14][15][16][17]19,21,23,37].…”
Section: Discussionsupporting
confidence: 92%
“…As for MALT lymphoma, the frequency observed in this study was similar to that of previous Korean data, and higher than the Japanese or USA data (Supplementary Table III) [4][5][6][7][8][9][10][11][12][13][14][15][16][17]19,21,23,37]. In agreement with previous findings, we found that the proportions of Korean patients with CLL/SLL and FL were low; this is in contrast to the increased rate of FL in Japan, where this subtype now accounts for 20% of all NHLs [12,22,27,45].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations